The Role of Leadership in Creating Virtuous and Compassionate Organizations: Narratives of Benevolent Leadership in an Anatolian Tiger - Karakas, Fahri (Journal of business ethics, 2013)
This study explores the role and potential of benevolent leadership in creating virtuous and compassionate organizations. A number of small and medium enterprises in Turkey, also called “The Anatolian Tigers”, have been experimenting with new ways of incorporating care and compassion at work. The study uses narrative inquiry to explore how benevolent leadership enhances collective performance and wellbeing in Anatolian Tigers. The paper reviews and integrates four streams of research associated with creating common good in organizations: Spirituality, morality, positivity, and community, and links each of these elements to creating virtuous and compassionate organizations through narrative inquiry. The paper proposes that benevolent leadership can contribute to the long-term health and sustainability of organizations through its four elements: spiritual depth, ethical sensitivity, positive engagement, and community responsiveness.